Selection - Graham Bell (Oxford University Press, 2008)
This book adopts an experimental approach to understanding the mechanisms of evolution and the nature of evolutionary processes, with examples drawn from microbial, plant and animal systems. It incorporates insights from remarkable recent advances in theoretical modelling, and the fields of molecular genetics and environmental genomics